1993
DOI: 10.1007/bf00268935
|View full text |Cite
|
Sign up to set email alerts
|

Immuno- and lectin histochemistry of epithelial subtypes and their changes in a radiation-induced lung fibrosis model of the mini pig

Abstract: Cell types of lung epithelia of mini pigs have been studied using a panel of monoclonal and polyclonal antibodies against cytokeratins (CKs) and vimentin and three lectins before and after radiation-induced fibrosis. In normal tissues, CK18 specific antibodies reacted above all with type II alveolar epithelial cells, while CK7 and pan CK-specific antibodies stained the whole alveolar epithelium. In bronchial epithelial cells, CKs 7, 8, 18 and focally CKs 4 and 13 as well as vimentin were found. Cell specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…Otherwise, ICAM-1 is reported to be induced on type II cells in vitro as a sign of differentiation towards a type I cell-like phenotype (Christensen et al 1993). Recently, we found a similar induction of other type I cell-specific antigens such as the pancadherin and changed lectin binding pattern on the surface of type II cells of fibrotic mini pigs (Kasper et al 1993;Kasper and Mtiller 1994).…”
Section: Discussionmentioning
confidence: 83%
“…Otherwise, ICAM-1 is reported to be induced on type II cells in vitro as a sign of differentiation towards a type I cell-like phenotype (Christensen et al 1993). Recently, we found a similar induction of other type I cell-specific antigens such as the pancadherin and changed lectin binding pattern on the surface of type II cells of fibrotic mini pigs (Kasper et al 1993;Kasper and Mtiller 1994).…”
Section: Discussionmentioning
confidence: 83%
“…In mini-pigs, additional staining of the capillary endothelium was found (Fig. 3f, corresponding double staining with the mini-pig endothelium-specific lectin Dolichus biflorus agglutinin, Kasper et al 1993b, revealed identity; not shown). Larger blood vessel endothelia exhibited no or only focal immunoreactivity for CD44s (Fig.…”
Section: Normal Tissuesmentioning
confidence: 86%
“…The animals (n=9) were sacrificed 9 months after irradiation (for details see [15]). Two control animals were included.…”
Section: Methodsmentioning
confidence: 99%